DINAMIKA HUKUM PERLINDUNGAN LINGKUNGAN HIDUP: TANTANGAN DAN INOVASI DALAM PENEGAKAN HUKUM - Ayuzauri; Apriliani, Rizka; Ihsan, Nur Muhammad (Jurnal Metrum, 2024)
The environment is a gift and mercy from God Almighty to the people and nation of Indonesia for life in all aspects. Environmental protection is an increasingly urgent issue in the current legal context. A hepalthy and sustainable environment is the right of every individual and is also a collective responsibility to protect our earth. The purpose of writing this journal is to find out what the challenges are in facing environmental law enforcement in Indonesia and to be able to innovate to increase the effectiveness of law enforcement environment in Indonesia. Then the method that the author chose in making this journal is a qualitative research method. Qualitative research is research that is used to investigate, discover, describe and explain the qualities or characteristics of social influences that cannot be explained, measured or described through a quantitative approach. The living environment is the sum of all objects and conditions in the space we occupy that affect our lives. The challenges faced in enforcing environmental law result in the ineffectiveness of supporting factors in enforcing environmental law. Many regulations have been issued by the government, but many challenges are still encountered in their implementation in the field.